Dans la ville instable - Laframboise, Alain (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract Highlighting the similarities between the convex mirror used by Pierre Granche in his series of photographs and Parmigianino's Self-Portrait in a Convex Mirror (1524), the mirror that Brunelleschi used in his experiments with portraying architecture as accurately as possible (Tavoletta, ca. 1415), or even the shield that Athena offered Perseus for his confrontation with the Gorgon, the author of this article proposes to approach this work by a play on associations. Ultimately, he sees in it, metaphorically, the image of a pendulum marking the time that Granche's photographs attempt to freeze.